ANALISIS PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN HOTEL BERBINTANG DI KOTA DENPASAR - Dewi, Ni Putu Shinta; Ernawatiningsih, Ni Putu Lisa (Jurnal Riset Akuntansi (JUARA), 2018)
This study aims to determine the effect of applying the effectiveness of accounting information systems, utilization of accounting information systems and suitability of tasks with accounting information systems to the performance of star hotel employees in the city of Denpasar. Determination technique of sample used in this research is technique of non probability sampling that is by purposive sampling. Criteria used as the basis of sample selection in this study are employees who work in the department of accounting, marketing and personnel at 3 and 4 star hotels in Denpasar City. Based on these criteria then obtained 105 samples used in this study. Data analysis technique used in this research is multiple regression analysis, with result of analysis obtained result that only variable effectiveness of accounting information system which have positive effect to hotel employee performance in Denpasar City.